Genetic Alterations in Intervertebral Disc Disease - Martirosyan, Nikolay L.; Patel, Arpan A.; Carotenuto, Alessandro; Kalani, M. Yashar S.; Belykh, Evgenii; Walker, Corey T.; Preul, Mark C.; Theodore, Nicholas (Frontiers in Surgery, 2016)
Background: Intervertebral disc degeneration (IVDD) is considered a multifactorial disease. The last two decades of research strongly demonstrate that genetic factors contribute about 75% of the IVDD etiology. Recent total genome sequencing studies have shed light on the various single nucleotide polymorphisms (SNPs) that are associated with IVDD. Aim: This review explores and presents updated information about the diversity of genetic factors in the inflammatory, degradative, homeostatic, and structural systems involved in the IVDD. Results: SNPs in the genes coding for structural proteins linked with IVDD or disc bulging include the Sp1 polymorphism of COL1A1, Trp3 polymorphism of COL9A3, several polymorphisms of COL11A1 and COL11A2, and a variable number tandem repeat polymorphism of ACAN. The rs4148941 SNP of CHST3 coding for an aggrecan sulfation enzyme is also associated with IVDD. The FokI, TaqI, and ApaI SNPs of the vitamin D receptor gene that is involved in chondrocyte functioning are also associated with IVDD. SNPs relevant to cytokine imbalance in IVDD include 889C/T of IL1a and 15T/A, as well as other SNPs (rs1800795, rs1800796, and rs1800797), of IL6, with effects limited to certain genders and populations. SNPs in collagenase genes include -1605G/D (guanine insertion/deletion) of MMP1, -1306C/T of MMP2, -1562C/T and a 5-adenosine (5A) variant (in the promotor region) of MMP3, -1562C/T of MMP9, and -378T/C of MMP-14. SNPs in aggrecanase genes include 1877T/U of ADAMTS-4 and rs162509 of ADAMTS-5. Among the apoptosis-mediating genes, 1595T/C of the caspase 9 gene, 1525A/G and 1595T/C of the TRAIL gene, and 626C/G of the death receptor 4 gene (DR4) are SNPs associated with IVDD. Among the growth factors involved in disc homeostasis, the rs4871857 SNP of GDF5 was associated with IVDD. VEGF SNPs -2578C/A and -634G/C could foster neovascularization observed in IVDD. Conclusion: Improved understanding of the numerous genetic variants behind various pathophysiological elements of IVDD could help advance personalized care and pharmacotherapeutic strategies for patients suffering from IVDD in the future.